Psychological Factors that Influence Decision Making at the Time of Purchase - Ramos-Galarza, Carlos (2024)
In the buying process there are several factors that determine consumer behavior, which is a central topic of interest in the Neuromarketing research line. In this article we reflect on psychological factors that influence this context: Following fashion stereotypes, the role of the frontal lobe, product purchase anxiety, the psychology behind colors, and personality traits that influence the buying process. The methodology followed was the review of classic research and theories that allowed us to analyze the psychological factors involved in the buying process. The article ends by discussing the need to understand the factors discussed in this research in order to better understand consumer behavior.